Mutational analysis of the simian immunodeficiency virus SIVmac nef gene. - Binninger, D (1991)
We are using site-directed mutagenesis of single viral genes to identify and analyze the genetic determinants of human and simian immunodeficiency virus pathogenicity. In a first approach, we have constructed a series of simian immunodeficiency virus SIVmac nef mutants by partial deletion and insertions in the nef gene, as this gene is a candidate gene for the establishment and maintenance of latency. nef insertion mutants replicated faster than wild-type SIVmac, suggesting that the nef gene product acts as a negative factor for replication. Surface phenotyping revealed that cultures permanently infected with nef mutants exhibit an enhanced expression of viral proteins on the outer cell surface. We have analyzed the properties of the mutant viruses in cell culture and intend to use rapidly replicating mutants (putatively unable to undergo latency) as model vaccine viruses in the rhesus monkey.